Outcome of Surgical Intervention of Spinal Tuberculosis Patients (Bangladesh Journal of Neurosurgery, 2024)
Background: Spinal tuberculosis is approximately 2% of all cases of tuberculosis.  Both conservative and surgical management are practiced for its management  worldwide. However, surgical management has excellent outcome.Objectives: The aim of the study was to document the clinical and neurological  outcomes of surgical intervention of spinal tuberculosis patients getting admitted in  a tertiary care hospital of Bangladesh.Materials & Method: This hospital based interventional study was conducted in  the department of Neurosurgery, Chittagong Medical College and Hospital for a period  of 12 months. Thirty-two cases with spinal tuberculosis underwent surgical  intervention were enrolled in the study. All patients were treated with standard anti-  TB drugs pre and postoperatively and were followed up regularly after surgery for 3  months. Neurological function and pain were evaluated preoperatively and  postoperatively by Frankel’s grade scale and visual analogue scale (VAS) respectively.  Post operative outcomes were finally assessed 3 months after operation.Results: Out of 32 cases, 2 were lost to follow up. Among the available 30 cases, 16  were men and 14 were women. The mean age was 36.10 (±13.70) years and age  range were 18 to 65 years. At the final follow-up, the VAS score significantly improved  from 6.97 (±1.87) preoperatively to 1.43 (±0.89) postoperatively (P < 0.001) and all  patients became pain free, with final VAS score 0-3. At the final follow-up, the ESR  and CRP significantly improved from preoperative status (P < 0.001). Twenty-nine  (96.7%) patients improved by at least one Frankel grade and remaining one (3.3%)  patient maintained their preoperative Frankel grade. Post operative deterioration was  not observed in any of the included case. Out of 11 cases with bowel bladder  dysfunction before surgery 10 (90.9%) recovered within three months.Conclusion: Surgical intervention was safe and had satisfactory results in terms of  symptomatic and neurological improvement.   Bang. J Neurosurgery 2023; 12(2): 94-101